2014
DOI: 10.1177/1082013214540672
|View full text |Cite
|
Sign up to set email alerts
|

Potentially synbiotic fermented beverage with aqueous extracts of quinoa (Chenopodium quinoa Willd) and soy

Abstract: The aim of this study was to develop a potentially synbiotic beverage fermented with Lactobacillus casei LC-1 based on aqueous extracts of soy and quinoa with added fructooligosaccharides (FOS). Five formulations with differing proportions of soy and quinoa extracts were tested. The viability of the microorganism, the pH, and the acidity of all formulations were monitored until the 28th day of storage at 5 ℃. The chemical composition of the extracts and beverages and the rheological and sensory properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 44 publications
5
36
2
6
Order By: Relevance
“…Growth of various Bifidobacterium and Lactobacillus strains in fermented milk with quinoa flour or aqueous extracts of quinoa, respectively, were not found to be significant in past studies (Bianchi et al, 2015;Casarotti et al, 2014). Quinoa did not affect microbial growth or provide protective benefits over a 28-day period (Bianchi et al, 2015;Casarotti et al, 2014) while El-Deeb et al (2014) found that the probiotic bacteria slightly decreased in count after seven days.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Growth of various Bifidobacterium and Lactobacillus strains in fermented milk with quinoa flour or aqueous extracts of quinoa, respectively, were not found to be significant in past studies (Bianchi et al, 2015;Casarotti et al, 2014). Quinoa did not affect microbial growth or provide protective benefits over a 28-day period (Bianchi et al, 2015;Casarotti et al, 2014) while El-Deeb et al (2014) found that the probiotic bacteria slightly decreased in count after seven days.…”
Section: Discussionmentioning
confidence: 88%
“…Quinoa did not affect microbial growth or provide protective benefits over a 28-day period (Bianchi et al, 2015;Casarotti et al, 2014) while El-Deeb et al (2014) found that the probiotic bacteria slightly decreased in count after seven days. These results coincide with our study which saw a decrease in the microbial vitality after 14 days.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations